Identifikasi Faktor Kesehatan Lingkungan Di Wilayah Rob Kelurahan Bandarharjo Kota Semarang - Yunita Rahmawati; Sulistyani Sulistyani; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2016)
Bandarharjo sub-district is an area that was inundated by the water that is caused by changes in land used in coastal areas, land subsidence and rising sea levels. Tidal inundation can affect the community, one of which is public health. Environmental health diseases was top ten Bandarharjo disease at the health center at 2015. The study aimed to identified environmental health factors in the tidal inundation area, sub-district Bandarharjo, Semarang city used cross sectional study approach. The number of respondents as many as 90 household. The determation of respondents used non random sampling. This study showed that the source of the cleanwater was 100% used artesist, fulfilling the water needs of more than 60 liters per day of 93 households (100%), the quality of the water as many as 46 samples (92 %) out of the 50 samples not met standard,  22 households out of 93 households (23.7%) had no toilets, poor sewerage as many as 100 %, trash can with open condition as many as 77 bins (82 , 8%) of 93 bins, trash can do not meet the criteria of 85 bins (91.4%) of the 93 bins, relative humidity as many as 4 houses (4.3%) of the 93 houses not met standard, poor house temperature as much as 71 houses (76.3%) of the 93 houses, the bad lighning as many as 43 houses (46.2%) of the 93 houses, poor floor conditions as much as 10 houses (10.8%) of the 93 houses, poor wall conditions as much as 51 houses (54.8%) of 93 houses, poorly ventilated area as much as 24 houses (25.8%) of the 93 houses, poor housing density as many as 72 houses (77.4%) of 93 houses. Enviromental health risk factor in tidal inundation area Bardarharjo sub-district that is poor water quality, there are still individual septic tank that does not qualify, all the sewage conditions respondents  did not qualify, the trash can of respondents still open, residential density are not met standard, and the house temperature of respondents are not met standard.